SHUKUR KHOLMIRZAEV’S LIFE AND CAREER - Kurbanov Dilshodbek Norkhidir o’g’li (Web of Journals Publishing, 2024)
The author of this article is a famous writer of Surkhandarya Shukur Kholmirzayev's work and love of country in his works, about love of country and his works talk about art and literary ideas.
Keywords: Alpomish, highlanders, Barchinoy, Boysun, literature, writer, creation, thinking, mentality, title.